Optimization Study of Multibeam Bathymetric Survey Line Based on Multiple Geometric Modeling - Wang, Keyuan; Ge, Xiaole; Li, Han; Liu, Xiangyi (Transactions on Computer Science and Intelligent Systems Research, 2025)
This paper focuses on multibeam bathymetric technology in the field of oceanographic survey and seabed mapping, and carries out a systematic study on the optimisation of survey line laying scheme. The purpose of this study is to improve the efficiency and accuracy of oceanographic surveys while reducing resource consumption and survey costs, and to reveal the importance of optimizing the survey line layout by analyzing the influence of the rationality of the survey line layout on the completeness and accuracy of the bathymetric data. Firstly, the importance of optimising the survey line layout is revealed by analysing the influence of the rationality of the survey line layout on the integrity and accuracy of the bathymetric data. On this basis, a series of models are constructed in this paper, including the planar coverage width calculation model, the adjacent strip overlap rate model and the slope coverage width model, which provide quantitative analysis tools for the survey line laying. In the case study of rectangular sea area and real sea area, key indicators such as the total length of the survey line, the percentage of the missed area and the total length of the part with overlap rate more than 20% are calculated to verify the effectiveness of the proposed method. The results show that the optimised line laying scheme can significantly improve the measurement efficiency and reduce the waste of resources, and provides important theoretical support and technical guidance for the practical operation of multibeam survey vessels.